Innovation, endogenous overinvestment, and incentive pay - Roman Inderst; Manuel Klein (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2009)
We analyze how two key managerial tasks interact: that of growing the business through creating new investment opportunities and that of providing accurate information about these opportunities in the corporate budgeting process. We show how this interaction endogenously biases managers toward overinvesting in their own projects. This bias is exacerbated if managers compete for limited resources in an internal capital market, which provides us with a novel theory of the boundaries of the firm. Finally, managers of more risky and less profitable divisions should obtain steeper incentives to facilitate efficient investment decisions.
urn:nbn:de:hebis:30-72931
Keywords: 330